Association of hyperuricemia with apolipoprotein AI and atherogenic index of plasma in healthy Chinese people: a cross-sectional study - Yan Duan; Xiaona Chang; Xiaoyu Ding; Yu An; Guang Wang; Jia Liu (BMC Cardiovascular Disorders, 2022)
Abstract Background The atherogenic index of plasma (AIP) is a predictor for cardiovascular diseases (CVD), while hyperuricemia is an independent risk factor for a variety of CVD. Apolipoprotein AI has been found to be a protective factor for CVD. However, the role of APO AI in the association between plasma uric acid and AIP among healthy Chinese people needs to be further explored. Aims To evaluate the relationship between blood uric acid and AIP level in healthy Chinese people. To evaluate the relationship between blood uric acid and Apolipoprotein AI in healthy Chinese people. Method A total of 3501 normal and healthy subjects who had physical examinations were divided into the hyperuricemia (HUA) group and the normouricemia (NUA) group. Result The AIP of HUA group was significantly higher than that of NUA group [0.17±0.30 vs. −0.08±0.29]. Apo AI (1.33 ± 0.21 vs. 1.47 ± 0.26 g/l) and HDL-c (1.12 ± 0.27 vs. 1.36 ± 0.33 mmol/l) were significantly lower in the HUA group than in the NUA group. LDL-C (2.81 ± 0.77 vs. 2.69 ± 0.73 mmol/l), Apo B (0.96 ± 0.20 vs. 0.89 ± 0.20 g/l), FBG (5.48 ± 0.48 vs. 5.36 ± 0.48 mmol/l) and HOMA-IR [2.75 (1.92–3.91) vs. 2.18 (1.50–3.12)] was significantly higher in HAU group than the NUA group. Increases in plasma UA were associated with increases in AIP (β = 0.307, p < 0.01) and decreases in Apo AI (β =  − 0.236, p < 0.01). Conclusion Hyperuricemia is an independent risk factor for high AIP level. Inhibition of Apolipoprotein AI may be one of the mechanisms of UA which is involved in the progression of cardiovascular disease.